Effects of Alchemilla vulgaris on haematology and antioxidant status of heatstressed quails during the late laying period - KÖSEMAN, A; AKDEMIR, F; ÜREMIŞ, N; ŞEKER, I; TÜRKÖZ, Y (Journal of the Hellenic Veterinary Medical Society, 2022)
The effects of Alchemilla vulgaris (AV) on haematology and serum, liver, and ovarian antioxidant status of heat-stressed quail in the late laying period were observed in this study. A 2×3 factorial design was used with 0, 1 and 3% AV fed in thermoneutral (TN) and heat stress (HS) conditions. A total of 150 quails were randomly assigned to six groups. The quails were located in temperature controlled rooms. The mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and platelet distribution width (PDW) obtained in quail fed 1% AV were higher than in 3% AV under both TN and HS conditions. Comparing 3% AV to 1% AV, the concentration of MCH obtained for 1% AV was higher in HS and lower in TN conditions. Besides, quails fed for 1% AV had a lower procalcitonin (PCT) value in HS than 3% AV but this PCT value was the same in TN. The serum malondialdehyde (MDA) was lower in 1% AV than 3% AV in both HS and TN. The ovarian MDA was lower in TN than HS. In both TN and HS conditions, the ovarian MDA value was determined higher for 1% AV than for 3% AV. The liver glutathione (GSH) value was higher in 1% AV than 3% AV in both TN and HS conditions. The Total Oxidant Capacity (TOS) value was found higher for 3% AV in TN and 1% AV in HS. The serum GSH, TOS, and oxidative stress index (OSI) values were lower for 3% AV compared to 1% AV for both TN and HS conditions, whereas for MDA value this was the opposite. The ovarium MDA and TOS values were lower for 3% AV than for 1% AV in both TN and HS. Also, the liver MDA, GSH, and Total Antioxidant Capacity (TAS) values were lower for 3% AV than for 1% AV in both TN and HS conditions. Finally, dietary AV has been shown to have a partial antioxidative effect on the defense system and also has effect on red blood cell profiles and platelet counts rather than white blood cell profiles.